Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Conference on Lasers and Electro-Optics 2012 2012
DOI: 10.1364/qels.2012.qth4f.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Chiral Plasmonic Oligomers

Abstract: First, the quartz glass substrate (Suprasil, Heraeus) is covered with a 70 nm thick spacer layer by spin-coating. A solidifiable photopolymer, PC403 (JCR, Japan), is used. A prebaking process is first carried out to remove the solvent from the polymer (increase of the baking temperature from 90 °C to 130 °C). A sufficiently long bake at a higher temperature (30 min at 180 °C) further hardens the layer. Next the three particle L-shape layer (dot diameter 200 nm, surface-to-surface distance 20 nm) and alignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
115
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 5 publications
2
115
1
Order By: Relevance
“…Our method will allow for large-area low-cost fabrication of high-quality complex plasmonic structures, such as oligomers [ 38 , 39 ] and chiral structures. [ 40 ] This technique will pave the road for real-life plasmonic applications like optical gas sensors, [ 41 , 42 ] biosensors, [ 22 , 43 ] leak detectors, [ 44 ] artifi cial nanonoses, [ 45 ] as well as chiral plasmonic enantiomer sensors [ 46 ] that could for example detect specifi cally glucose, which is a handed molecule. Our method is very fl exible towards other structure geometries, scalable to even larger areas, very reproducible, and adaptable for other substrate materials and metals.…”
Section: Doi: 101002/adma201202109mentioning
confidence: 99%
“…Our method will allow for large-area low-cost fabrication of high-quality complex plasmonic structures, such as oligomers [ 38 , 39 ] and chiral structures. [ 40 ] This technique will pave the road for real-life plasmonic applications like optical gas sensors, [ 41 , 42 ] biosensors, [ 22 , 43 ] leak detectors, [ 44 ] artifi cial nanonoses, [ 45 ] as well as chiral plasmonic enantiomer sensors [ 46 ] that could for example detect specifi cally glucose, which is a handed molecule. Our method is very fl exible towards other structure geometries, scalable to even larger areas, very reproducible, and adaptable for other substrate materials and metals.…”
Section: Doi: 101002/adma201202109mentioning
confidence: 99%
“…These effects, which may be useful for biomolecular sensing 9,12 and are fundamentally interesting, are nevertheless limited in magnitude. Stronger effects could be obtained in systems of achiral nanoparticles arranged in a chiral superstructure with strong interparticle interaction [13][14][15][16] . Recently, Kotov and colleagues 17 demonstrated that the chiroptical activity of a chiral particle dimer is intense enough to monitor on a single nanoparticle level.…”
mentioning
confidence: 99%
“…The novel DNA-based assembly method developed here paves the way for fabricating other interesting plasmonic structures, such as chiral nanostructures. 41,42 Methods Chemicals and gold nanosphere assembly. Gold(III) chloride trihydrate (99.9 þ %) and tris(2-carboxyethyl)phosphine hydrochloride (TCEP) were purchased from Sigma Aldrich.…”
mentioning
confidence: 99%